2017
DOI: 10.1007/s40801-017-0121-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Variability in Medications Contributing to Polypharmacy in Long-Term Care Facilities

Abstract: BackgroundResearch into which medications contribute to polypharmacy and the variability in these medications across long-term care facilities (LTCFs) has been minimal.ObjectiveOur objective was to investigate which medications were more prevalent among residents with polypharmacy and to determine the variability in prescribing of these medications across LTCFs.MethodsThis was a cross-sectional study of 27 LTCFs in regional and rural Victoria, Australia. An audit of the medication charts and medical records of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 44 publications
1
21
1
Order By: Relevance
“…Our study findings are consistent with other research in RACSs suggesting that PPI use is highly prevalent [68]. Furthermore, our finding that residents taking high-dose PPIs had high levels of polypharmacy and medication regimen complexity compared to low/standard-dose users is consistent with previous RACS research that found PPIs were taken by 72% of residents receiving nine or more regular medications compared to 36% receiving fewer than nine medications [26]. Previous research has predominantly investigated prevalence of PPI use in RACSs using defined daily doses or without assessing dose.…”
Section: Discussionsupporting
confidence: 92%
“…Our study findings are consistent with other research in RACSs suggesting that PPI use is highly prevalent [68]. Furthermore, our finding that residents taking high-dose PPIs had high levels of polypharmacy and medication regimen complexity compared to low/standard-dose users is consistent with previous RACS research that found PPIs were taken by 72% of residents receiving nine or more regular medications compared to 36% receiving fewer than nine medications [26]. Previous research has predominantly investigated prevalence of PPI use in RACSs using defined daily doses or without assessing dose.…”
Section: Discussionsupporting
confidence: 92%
“…Direct-acting oral anticoagulants were not identified in this study; however, future studies should investigate the impact of these medications on the prescribing of warfarin and other anticoagulants. Although statin use in NHs increased over time points, its use remains low in comparison with recent findings internationally in Australian [8,41], Canadian [42] and European [3] NHs, which found a prevalence of up to 40%. A review of randomized controlled trials (RCTs) and retrospective studies of statin use for secondary prevention in community-dwelling older people identified overall benefit in reduction of cardiovascular events and mortality in those aged ≥ 65 to < 75 years but minimal justification for its use in those aged > 85 years [43].…”
Section: Discussioncontrasting
confidence: 58%
“…Between 13 and 74% of residents in LTCFs take nine or more regular medications [7]. Half of residents are prescribed antithrombotics and up to 80% are prescribed at least one cardiovascular agent [7][8][9]. Compared with older people in the community, residents of LTCFs are less likely to be prescribed medications for stroke (aspirin and other anticoagulants) and for heart disease [β-blockers, angiotensinconverting enzyme inhibitors (ACEIs) and aspirin] [10,11].…”
Section: Key Pointsmentioning
confidence: 99%
“…Second, according to Delbaere's algorithm, polypharmacy confers high falls risk in residents who are unable to stand unaided. Cardiovascular medications have also been strongly linked to polypharmacy (Jokanovic et al, 2017). This could also be one possible explanation why residents at high falls risk were more likely to be using two or more psychotropics, but not using one psychotropic medication.…”
Section: Discussionmentioning
confidence: 99%